(untitled) - Coffman, James R. (Bolton, Mass., 2005)
While academic freedom enables members of the academic community to pursue their work, it can also become a source of conflict between faculty members as well as individual faculty and administrators. In most instances, conflict in an academic environment requires only a clear system in which to pursue resolution. The creation of such a conflict management system will ideally correct misunderstandings before they lead to greater problems, and as such, it is of crucial importance to every higher education institution.
Keywords: College personnel management,Communication in education,Quản lý nhân sự Trường cao đẳng,Giao tiếp trong giáo dục